Investigation of the Effictiveness of Group Play Therapy Training With Cognitive-Behavioral Approach on the Social Skills of Students With Intellectual Disability - Mohammad Ashori; Masoume Yazdanipour (Journal of Rehabilitation, 2018)
Objective Intellectual disability is a common neurodevelopmental disorder which leads to lower social activities, skills and life quality. It seems that play therapy could improve social skills of students with intellectual disability. Play is one of the important methods for social skills training to students with intellectual disability. Group play therapy enhances social skills like leadership among children. Cognitive-behavioral play therapy has been proposed since several decades ago as an intervention program for developing social relationships and skills in children with intellectual disability. Cognitive-Behavioral Play Therapy (CBPT) is a developmentally sensitive adaptation of cognitive-behavioral therapy. In CBPT, play is a medium to communicate and indirectly teach empirically-supported techniques to children in an engaging way. So, it is important to plan suitable training programs such as group play therapy training program for improving social skills of children with intellectual disability. The purpose of the present study was to investigate of the efficacy of group play therapy training with cognitive-behavioral approach on the social skills of students with intellectual disability in Isfahan City, Iran. Materials & Methods The present research was a quasi-experimental study with pretest, post-test design and control group. The participants were 22 students with intellectual disability aged 7-11 years in 2017-2018 academic year. They belonged to middle socio-economical class. Subjects were selected by convenience sampling method from school of Shahidan Nouri in Isfahan. They were divided into experimental and control groups, each group consisting of 14 students. The experimental group received group play therapy training program in 7 sessions (each session 40 minutes), while control group did not participate in this program but participated in common group play therapy program in the school. The study instrument was the social skills scale of Matson. Social skills scale was completed by parents for all subjects in pretest and post-test. The relevant data were collected through the questionnaire before and after the training sessions. Multivariate Analysis of Covariance (MANCOVA) was performed in SPSS V. 23. Results first, normality of variables and contingency of variance and covariance assumptions were tested. The Kolmogorov-Smirnov test showed that all variables were normally distributed (P>0.05). Also, Box test confirmed contingency of variance-covariance assumption. So, assumptions of MANCOVA test were confirmed and could be used for data analysis. The results of MANCOVA showed that group play therapy training with cognitive-behavioral approach program had a significant effect on the social skills of students with intellectual disability (P<0.001). The results also revealed that group play therapy training program had a significant effect on all subscales of social skills (appropriate social behavior, asocial behavior, aggressive and impulsive behavior, superiority and self-confidence, communication with peers) in these students (P<0.001). It can be stated that according to Eta square, 67%, 55%, 61%, 56%, 62%, and 55% of variations in components of appropriate social behavior, asocial behavior, aggressive and impulsive behavior, superiority and self-confidence, communication with peers, and social skills, respectively, can be explained by the subjects’ participation in group play therapy training program. Conclusion Group play therapy training program with cognitive-behavioral approach improved the social skills of students with intellectual disability. In other words, applying this training program has been associated with effective and positive outcomes, because social skills of the control group did not shown significant improvement. Therefore, paying attention to the group play therapy training program with cognitive-behavioral approach is essential and planning for providing training of this type of group play therapy program for children and students with intellectual disability is of particular importance.